The Influence of Nurses’ Workload and Self-Efficacy on the Implementation of Patient-Centered Care - Ratna Indrawati; Irma Nurfauzia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Patient-centered care (PCC) is a healthcare approach that places the patient at the center of care by considering their needs, values, and preferences. However, in practice, the implementation of PCC in hospitals still faces various challenges, particularly related to nurses' workload and psychological factors such as self-efficacy. This study aims to analyze the influence of nurses' workload and self-efficacy on the implementation of patient-centered care in a Type B Hospital in Bekasi. This study used a quantitative design with a cross-sectional approach. The sample was 45 nurses working in the intensive care unit. Data were collected using a questionnaire and analyzed using multiple linear regression with the help of SPSS. The results showed that the regression model was significant with an F value of 25.662 (p < 0.001). The R Square value of 0.550 indicates that workload and self-efficacy together explain 55% of the variation in PCC implementation. Partially, workload had a significant negative effect on PCC (β = -0.467; p < 0.001), while self-efficacy had a significant positive effect on PCC (β = 0.476; p < 0.001). The conclusion of the study shows that optimal workload management and increasing nurses' self-efficacy are very important to improve the implementation of patient-centered care in hospitals.